Multilayer structure, method for preparing the same, and packaging container

By designing a starch layer containing high-content starch and amylose, an adhesive layer of low-density thermoplastic resin and a base material layer with high tensile elastic modulus in a multilayer structure, and using coextrusion and side coating processes to form a laminated structure, the problem of reducing peel strength caused by the expansion and contraction of the starch resin layer in a low-humidity environment is solved, and high peel strength and good gas barrier properties are achieved in a low-humidity environment.

CN114340889BActive Publication Date: 2025-03-04PLANTIC TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080064032.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-13
Filing Date
2020-09-11
Publication Date
2025-03-04
Estimated Expiration
2040-09-11

AI Technical Summary

Technical Problem

The multilayer structure containing the starch resin layer is prone to stretching and contracting due to moisture absorption and release of the starch resin layer in a low humidity environment, resulting in a significant reduction in the peel strength from the adhesive resin layer.

Method used

The multi-layer structure is designed, in which the starch layer (A) consists of a material containing more than 20% starch and more than 50% amylose, the adhesive layer (B) consists of a thermoplastic resin having a density of less than 0.920 g/cm3, and the base material layer (C) has a tensile elastic modulus of more than 100 MPa, and a laminated structure is formed by coextrusion and side coating processes.

Benefits of technology

Even in a low humidity environment, the multilayer structure can maintain a high peel strength, avoiding the reduction of peel strength between the adhesive layer and the starch layer, and also having good gas barrier and biodegradability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114340889B_ABST
    Figure CN114340889B_ABST
Patent Text Reader

Abstract

The present invention relates to a multilayer structure, which sequentially comprises a starch layer (A), an adhesive layer (B) and a substrate layer (C), wherein the material constituting the starch layer (A) comprises starch and water, and the material constituting the adhesive layer (B) comprises a substrate having a density of 0.920 g / cm 3 The following thermoplastic resin, the acid value of the material constituting the adhesive layer (B) is 0.3 mgKOH / g or more, and the base material layer (C) is a layer with a tensile elastic modulus of 100 MPa or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a multilayer structure, a method for preparing the multilayer structure, and a packaging container containing the multilayer structure. Background Art

[0002] Resin layers with starch as the main component are biodegradable and have excellent gas barrier properties, so they are widely used in containers for packaging food.

[0003] The resin layer with starch as the main component has high hydrophilicity and is easily significantly impaired in barrier properties due to the influence of humidity. Therefore, when barrier properties are particularly required, it is necessary to form multiple layers with a water-resistant material (Patent Documents 1 and 2). As a method for forming multiple layers, from the perspective of productivity, an extrusion coating method using an outer layer material is often used. As the outer layer material, PET, PE, PP, nylon, polyvinyl chloride, polyvinylidene chloride, etc. are used.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application No. 2015-508341,

[0007] Patent Document 2: Japanese Patent Application Publication No. 2015-533733. Summary of the invention

[0008] Problems to be solved by the invention

[0009] About the preparation of the multilayer structure containing starch resin layer, there is the record that starch resin and adhesive resin can be used in extrusion coating method in the past technology.But starch resin layer is affected by external temperature and humidity, can expand and contract more than several % by absorbing and releasing moisture.Therefore, particularly in the case of keeping under low humidity, owing to being different from the expansion and contraction rate of adhesive resin layer, there is the problem of remarkable reduction of peel strength.

[0010] Therefore, an object of the present invention is to provide a multilayer structure having a starch resin layer that can maintain peel strength even when stored under low humidity, a method for producing the multilayer structure, and a packaging container containing the multilayer structure.

[0011] Means of solving problems

[0012] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved, thereby completing the present invention. That is, the present invention includes the following preferred aspects.

[0013] [1] A multilayer structure comprising, in order, a starch layer (A), an adhesive layer (B) and a substrate layer (C), wherein:

[0014] The material constituting the starch layer (A) contains starch and water.

[0015] The material constituting the adhesive layer (B) has a density of 0.920 g / cm 3 The following thermoplastic resins,

[0016] The base material layer (C) is a layer having a tensile elastic modulus of 100 MPa or more.

[0017] [2] The multilayer structure according to [1], wherein the content of starch in the material constituting the starch layer (A) is 20% by mass or more, and the content of amylose in the starch is 50% by mass or more.

[0018] [3] The multilayer structure according to [1] or [2], wherein the material constituting the starch layer (A) contains at least one water-soluble polymer.

[0019] [4] The multilayer structure according to any one of [1] to [3], wherein the material constituting the starch layer (A) contains at least one kind of clay.

[0020] [5] The multilayer structure according to any one of [1] to [4], wherein the acid value of the material constituting the adhesive layer (B) is 0.3 mgKOH / g or more.

[0021] [6] The multilayer structure according to any one of [1] to [5], wherein the material constituting the adhesive layer (B) contains a polyolefin-based polymer.

[0022] [7] The multilayer structure according to any one of [1] to [6], wherein the material constituting the substrate layer (C) contains at least one selected from polyethylene terephthalate, polylactic acid, polyethylene, polypropylene, cellophane, aromatic polyester and polybutylene succinate.

[0023] [8] A method for preparing a multilayer structure according to any one of [1] to [7], comprising:

[0024] a step of co-extruding the adhesive layer (B) and the substrate layer (C), and

[0025] Next, the adhesive layer (B) is coated on the starch layer (A).

[0026] [9] A method for producing a multilayer structure according to any one of [1] to [7], comprising:

[0027] The step of extruding the adhesive layer (B), and

[0028] Next, a step is performed to apply an adhesive layer (B) between the starch layer (A) and the base material layer (C).

[0029]

[10] A packaging container comprising the multilayer structure according to any one of [1] to [7].

[0030] Effects of the Invention

[0031] The multilayer structure of the present invention can provide a multilayer structure having a starch resin layer that can maintain peel strength even when stored under low humidity. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] [ Figure 1 ] is a schematic diagram showing a twin-screw extruder used for producing the starch layer (A) in Examples. DETAILED DESCRIPTION

[0033] The multilayer structure of the present invention comprises a starch layer (A), an adhesive layer (B) and a substrate layer (C) in sequence. The material constituting the starch layer (A) comprises starch and water, and the material constituting the adhesive layer (B) comprises a substrate layer having a density of 0.920 g / cm 3 The following thermoplastic resins, the acid value of the material constituting the above-mentioned adhesive layer (B) is 0.3 mgKOH / g or more, and the base material layer (C) is a layer with a tensile elastic modulus of 100 MPa or more.

[0034] <Starch layer (A)>

[0035] The material constituting the starch layer (A) contains starch (A1) and water. In the starch layer (A), the content of starch (A1) is preferably 20% by mass or more, and the content of straight-chain starch in the starch (A1) is 50% by mass or more. In addition, the content of starch (A1) in the material constituting the starch layer (A) is preferably 50 to 98% by mass, more preferably 70 to 98% by mass. If the content of starch (A1) is within the above range, there is a tendency to easily obtain good gas barrier properties.

[0036] [Starch (A1)]

[0037] Examples of the starch (A1) include starch derived from cassava, corn, potato, sweet potato, sago, tapioca, sorghum, soybean, bracken, lotus root, water chestnut, wheat, rice, oats, kudzu root, peas, and the like.

[0038] Starch (A1) may be a modified starch. From the viewpoint of the content of amylose, the raw material of the modified starch is preferably starch derived from corn (maize) or cassava, and more preferably starch derived from corn. Examples of modified starch include etherified starch, esterified starch, cationized starch, and cross-linked starch. The material constituting the starch layer (A) may contain one or more of these modified starches.

[0039] Examples of the etherified starch include alkyl etherified starches such as methyl etherified starch, carboxyalkyl etherified starches such as carboxymethyl etherified starch, and hydroxyalkyl etherified starches such as etherified starches having a hydroxyalkyl group having 2 to 6 carbon atoms. Allyl etherified starches may also be used.

[0040] Examples of esterified starch include esterified starch having a structural unit derived from carboxylic acid, such as esterified starch having a structural unit derived from acetic acid, esterified starch having a structural unit derived from maleic anhydride, esterified starch having a structural unit derived from phthalic anhydride, esterified starch having a structural unit derived from octenyl succinic anhydride, and esterified starch having a structural unit derived from dicarboxylic anhydride, such as esterified starch having a structural unit derived from nitric acid, phosphate, and urea phosphate. Other examples include xanthate-esterified starch and acetoacetate-esterified starch.

[0041] Examples of the cationized starch include a reaction product of starch and 2-diethylaminoethyl chloride, and a reaction product of starch and 2,3-epoxypropyltrimethylammonium chloride.

[0042] Examples of the cross-linked starch include formaldehyde cross-linked starch, epichlorohydrin cross-linked starch, phosphoric acid cross-linked starch, and acrolein cross-linked starch.

[0043] Among these modified starches, from the viewpoint of easily suppressing the decrease in peel strength under low humidity, etherified starch having a hydroxyalkyl group having 2 to 6 carbon atoms, esterified starch having a structural unit derived from a dicarboxylic anhydride, or a combination thereof is preferred, and hydroxyethyl etherified starch, hydroxypropyl etherified starch, hydroxybutyl etherified starch, esterified starch having a structural unit derived from maleic anhydride, esterified starch having a structural unit derived from phthalic anhydride, esterified starch having a structural unit derived from octenyl succinic anhydride, or a combination thereof is more preferred.

[0044] The etherified starch having a hydroxyalkyl group having 2 to 6 carbon atoms can be obtained by reacting an alkylene oxide with starch. Examples of the alkylene oxide include ethylene oxide, propylene oxide, and butylene oxide. The average number of hydroxyl groups used for modification is preferably 0.05 to 2 per glucose unit in the starch.

[0045] Modified starch can be prepared by modifying starch having a specified amylose content using methods known in the art, or commercially available modified starch can be used. Examples of representative commercial products of modified starch include, for example, ECOFILM (registered trademark) or National 7 (registered trademark) as hydroxypropyl etherified starch available from Ingredion.

[0046] For the starch (A1) contained in the starch layer (A), the content of amylose in the starch (A1) is preferably 50% by mass or more, more preferably 55% by mass or more, and further preferably 60% by mass or more. When the content of amylose in the starch (A1) is 50% by mass or more, the viscosity is suppressed and sheet formability is easily obtained. In addition, for starch (A1), the content of amylose in the starch (A1) is usually 90% by mass or less. The content of amylose in the starch (A1) can be measured, for example, by the iodine colorimetric method described in "Starch 50 No.4 158-163 (1998)". When the starch layer (A) contains more than two kinds of starch (A1), the amylose content of the starch (A1) refers to the weighted average value, i.e., the average amylose content, taking into account the composition ratio of more than two kinds of starch.

[0047] The water content in the starch (A1) is preferably 2 to 15% by mass. The water content can be determined, for example, using a halogen moisture meter.

[0048] [water]

[0049] The material constituting the starch layer (A) contains water. The water content in the starch layer (A) is preferably 5 to 25% by mass, more preferably 10 to 15% by mass. If the water content is within the above range, there is a tendency for excellent thermoformability.

[0050] [Water-soluble polymer]

[0051] The material constituting the starch layer (A) may contain at least one water-soluble polymer. The content of the above-mentioned water-soluble polymer in the material constituting the starch layer (A) is preferably 2 to 50% by mass, more preferably 2 to 35% by mass. If the content of the water-soluble polymer is within the above range, there is a tendency to easily obtain strength at low temperatures. As water-soluble polymers, polyvinyl alcohol (A2), polyethylene oxide, polyacrylamide, etc. can be listed, wherein, from the viewpoint of mechanical properties, polyvinyl alcohol (A2) is preferred. The saponification degree of polyvinyl alcohol (A2) is preferably 80 to 99.8 mol%. When the saponification degree of polyvinyl alcohol (A2) is within the above range, sufficient strength and oxygen barrier properties are easily obtained. The saponification degree is more preferably 85 mol% or more, and further preferably 88 mol% or more. It should be noted that in this specification, the saponification degree refers to the molar fraction of the hydroxyl group in polyvinyl alcohol (A2) relative to the sum of the hydroxyl group and the ester group. The above-mentioned saponification degree can be obtained, for example, by quantifying the residual acetic acid group in the sample with sodium hydroxide.

[0052] The polyvinyl alcohol (A2) may also contain other monomer units in addition to the vinyl alcohol unit. Examples of other monomer units include monomer units derived from ethylenically unsaturated monomers. Examples of ethylenically unsaturated monomers include: α-olefins such as ethylene, propylene, n-butene, isobutylene, and 1-hexene, acrylic acid and its salts, unsaturated monomers having an acrylate group, methacrylic acid and its salts, unsaturated monomers having a methacrylate group, acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetoneacrylamide, acrylamidepropanesulfonic acid and its salts, acrylamidopropyldimethylamine and its salts (e.g., quaternary ammonium salts), methacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, Methacrylamide propanesulfonic acid and its salts, methacrylamide propyl dimethylamine and its salts (such as quaternary ammonium salts), vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether, 2,3-diacetoxy-1-vinyloxypropane, vinyl cyanides such as acrylonitrile and methacrylonitrile, vinyl halides such as vinyl chloride and vinyl fluoride, vinyl halides such as vinylidene chloride and vinylidene fluoride (vinylidene chloride) halide), allyl compounds such as allyl acetate, 2,3-diacetoxy-1-allyloxypropane, and allyl chloride, unsaturated dicarboxylic acids such as maleic acid, itaconic acid, and fumaric acid, and their salts or esters, vinyl silyl compounds such as vinyltrimethoxysilane, isopropenyl acetate, vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl versatate, vinyl caproate, vinyl caprylate, vinyl laurate, vinyl palmitate, vinyl stearate, vinyl oleate, vinyl benzoate, and other vinyl ester monomers. The content of other monomer units is preferably 10 mol% or less, and more preferably 5 mol% or less. The monomer units in polyvinyl alcohol can be, for example, 13 C-NMR or IR method etc.

[0053] The preparation method of the polyvinyl alcohol (A2) is not particularly limited. For example, a method of converting a vinyl alcohol unit into a vinyl alcohol unit by copolymerizing a vinyl alcohol monomer with other monomers and saponifying the obtained copolymer can be cited. As the polymerization mode during copolymerization, intermittent polymerization, semi-intermittent polymerization, continuous polymerization, semi-continuous polymerization, etc. can be cited. As the polymerization method, known methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization can be cited. The saponification of the copolymer can be applied by known methods. For example, it can be carried out in a state where the copolymer is dissolved in alcohol or aqueous alcohol. The alcohol that can be used at this time is preferably, for example, a lower alcohol such as methanol and ethanol.

[0054] The viscosity of the polyvinyl alcohol (A2) at 20° C. in a 4% aqueous solution measured in accordance with JIS Z 8803 is preferably 1 mPa·s or more, more preferably 2 mPa·s or more, further preferably 3 mPa·s or more, preferably 45 mPa·s or less, more preferably 35 mPa·s or less. When the viscosity of the polyvinyl alcohol (A2) is at least the above lower limit and at most the above upper limit, sufficient strength and oxygen barrier properties are easily obtained.

[0055] [clay]

[0056] The material constituting the starch layer (A) may contain at least one kind of clay. Examples of the clay include synthetic or natural layered silicate clays, such as montmorillonite, bentonite, beidellite, mica, hectorite, saponite, nontronite, sauconite, vermiculite, ledikite, magadiite, kenyaite, stevensite, volkonskoite, and mixtures thereof.

[0057] In some embodiments, the above-mentioned clay may be modified to be hydrophobic or hydrophilic.

[0058] In some embodiments, the layered silicate clay may be modified to be hydrophobic or hydrophilic.

[0059] "Hydrophobic clay" or "layered silicate clay modified to be hydrophobic" is preferably a clay modified by exchange with a surfactant containing a long chain alkyl group. The long chain alkyl group may contain more than 4, more than 5 or more than 6 carbon atoms per chain. Preferred surfactants contain long chain alkyl ammonium ions, such as mono- or di-C 12 -C 22 Alkyl ammonium ion. Preferably, the long chain alkyl group does not contain polar substituents, such as hydroxyl and carboxyl groups. Preferred examples of clays modified to be hydrophobic are NANOMER I.40P from Nanocor, Inc. or CLOISITE (registered trademark) 20A or CLOISITE (registered trademark) 25A from Southern Clay Products, Inc.

[0060] The content of clay in the material constituting the starch layer (A) is preferably 0.1 to 5% by mass, more preferably 0.1 to 3% by mass, and further preferably 0.5 to 2% by mass. When clay is contained in an amount within the above range, transparency, flexibility, tensile strength, impact resistance, and / or tensile properties tend to be easily improved.

[0061] [Other additives]

[0062] The material constituting the starch layer (A) may contain a plasticizer, a moisturizer, a lubricant, and other additives.

[0063] Examples of the plasticizer include polyols, polyethylene glycol, epoxidized linseed oil, epoxidized soybean oil, tributyl citrate, 2,2,4-trimethylpentanediol diisobutyrate, and acetyl triethyl citrate. The content of the plasticizer in the material constituting the starch layer (A) is preferably 20% by mass or less.

[0064] As the humectant, for example, carrageenan, xanthan gum, gum arabic, guar gum, gelatin, and triacetin can be cited. The humectant sometimes also functions as a water-binding material or a gelling agent. In the material constituting the starch layer (A), the content of the humectant is preferably 20% by mass or less.

[0065] Examples of lubricants include fatty acids and fatty acid salts. Lubricants derived from C12 to 22 fatty acids are particularly preferred. Specifically, examples include stearic acid, sodium salts of stearic acid, and potassium salts of stearic acid. In the material constituting the starch layer (A), the content of the lubricant is preferably 1.5% by mass or less.

[0066] <Adhesive layer (B)>

[0067] The material constituting the adhesive layer (B) has a density of 0.920 g / cm 3 The following thermoplastic resins may be contained. One or more thermoplastic resins may be contained. The material constituting the adhesive layer (B) does not contain a thermoplastic resin having a density of 0.920 g / cm 3 In the case of thermoplastic resins below 0.9182 g / cm, it is difficult to suppress the decrease in peel strength under low humidity. 3 Below, more preferably 0.9100 g / cm 3 Below, more preferably 0.9000 g / cm 3 Below, more preferably 0.8900 g / cm 3 In addition, the density is preferably 0.5 g / cm 3 More preferably 0.85 g / cm 3 If the material constituting the adhesive layer (B) has a density of 0.920 g / cm 3 Here, when the material constituting the adhesive layer (B) contains two or more thermoplastic resins, as long as the density of at least one thermoplastic resin is 0.920 g / cm 3In this case, the weighted average value considering the composition ratio of two or more thermoplastic resins is preferably 0.920 g / cm 3 The density can be measured, for example, by the method described in the examples below.

[0068] The acid value of the material constituting the adhesive layer (B) is 0.3mgKOH / g or more. If the above-mentioned acid value is lower than 0.3mgKOH / g, it is possible that the bonding strength between the starch layer (A) and the adhesive layer (B) cannot be fully obtained, and the peel strength under low humidity is also reduced. The acid value of the material constituting the adhesive layer (B) is preferably 0.4mgKOH / g or more, more preferably 0.5mgKOH / or more, further preferably 0.6mgKOH / g or more, and further preferably 1.5mgKOH / g or more. In addition, the acid value is preferably 5mgKOH / g or less, more preferably 3mgKOH / g or less. If the acid value of the material constituting the adhesive layer (B) is above the above-mentioned lower limit, the bonding strength between the starch layer (A) and the adhesive layer (B) becomes sufficient, and if it is below the above-mentioned upper limit, the reaction during thermoforming is appropriately carried out, and it is therefore difficult to cause poor molding. The above-mentioned acid value can be measured, for example, by the method described in the embodiments described later. When the material constituting the adhesive layer (B) contains two or more thermoplastic resins, the acid value of the material means an acid value measured for the material as a mixture as described in Examples below.

[0069] It should be noted that the acid value is related to the amount of the acid in the adhesive layer (B). It is believed that the acid in the adhesive layer (B) obtains adhesion by reacting with the hydroxyl group on the surface of the starch layer (A), and is particularly helpful for initial bonding strength and peel strength under low humidity. It is believed that the initial bonding strength and peel strength under low humidity are related to the effect of the reaction of the acid in the above-mentioned adhesive layer (B) with the hydroxyl group in the starch layer (A) and the effect brought by the compatibility of the starch layer (A) and the adhesive layer (B). Therefore, in order to achieve good adhesion, as the material of the adhesive layer (B) constituting the multilayer structure of the present invention, it is believed that an acid value of more than 0.3mgKOH / g is required, more preferably more than 0.4mgKOH / g. The acid value of the material constituting the adhesive layer (B) can be adjusted to more than the above-mentioned lower limit value, for example, by appropriately adjusting the type and composition ratio of the structural unit constituting the thermoplastic resin described later.

[0070] [Thermoplastic resin]

[0071] The material constituting the adhesive layer (B) contains a thermoplastic resin. As the thermoplastic resin, for example, polyolefin polymers, polyester polymers, polyamide polymers, etc. can be listed, preferably containing polyolefin polymers, wherein preferably containing modified polyolefin polymers. As modified polyolefin polymers, resins obtained by modifying polyolefins having carbon atoms of about 2 to 20 such as ethylene, propylene, 1-butene, 3-methyl-1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, etc., copolymers of vinyl compounds and olefins such as vinyl acetate, vinyl chloride, acrylic acid, methacrylic acid, acrylic acid esters, methacrylates, polystyrene, and resins obtained by modifying polyolefin copolymers such as ethylene-propylene copolymers, ethylene-propylene-diene copolymers, ethylene-1-butene copolymers, and propylene-1-butene copolymers can be listed as representative substances. As a method of modification, modification based on grafting reaction conditions can be listed. As the material used for the graft reaction, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, isocrotonic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, and tetrahydrophthalic acid can be listed, and derivatives such as acyl halides, amides, imides, anhydrides, and esters can be listed. Specifically, maleic chloride, maleimide, maleic anhydride, citraconic anhydride, monomethyl maleate, dimethyl maleate, glycidyl maleate, etc. can be listed. If these modified polyolefin polymers are used, it is easy to suppress the yellowing of the multilayer structure when it is used.

[0072] On the other hand, from the viewpoint of suppressing yellowing of the multilayer structure during use, the content of the urethane resin in the material constituting the adhesive layer (B) is preferably 50% by mass or less, preferably 10% by mass or less, and most preferably 0% by mass.

[0073] As the modified polyolefin polymer, from the viewpoint of reactivity and sanitation as a food packaging material, it is preferred to use a resin modified with an unsaturated dicarboxylic acid or its anhydride, particularly maleic acid or its anhydride. As the modified resin, preferably an ethylene resin, a propylene resin, an ethylene-propylene copolymer or an ethylene-1-butene copolymer. Therefore, in a preferred embodiment of the present invention, it is preferred to use a polyolefin polymer modified with maleic anhydride, i.e., a polyolefin polymer having a structural unit derived from maleic anhydride.

[0074] <Base layer (C)>

[0075] The substrate layer (C) is a layer having a tensile modulus of elasticity of 100 MPa or more. The tensile modulus of elasticity is 100 MPa or more, preferably 200 MPa or more, more preferably 300 MPa or more, more preferably 500 MPa or more, more preferably 1000 MPa or more, particularly preferably 2000 MPa or more, and more particularly preferably 3000 MPa or more. The elastic modulus can be measured by the method described in the following embodiments, for example. Usually, the elastic modulus is 8000 MPa or less. In order to make the tensile modulus of elasticity of the substrate layer (C) above the lower limit, the type and composition ratio of the material constituting the substrate layer (C) can be adjusted to above the lower limit. If the elastic modulus is lower than 100 MPa, the substrate layer strength is insufficient and substrate fracture is likely to occur. The material constituting the substrate layer (C) preferably contains at least one selected from polyethylene terephthalate (PET), polylactic acid (PLA), polyethylene, polypropylene, cellophanes, aromatic polyesters and polybutylene succinate (PBS). The content of the above-mentioned material in the substrate layer (C) is preferably 10~100 mass %, more preferably 20~90 mass %. The material constituting the substrate layer (C) may also contain other materials such as polyolefin, nylon, polyvinyl chloride, polyvinylidene chloride. When the substrate layer (C) contains other materials, the content of the other materials in the substrate layer (C) may preferably be 5~50 mass % (the sum of all materials in the substrate layer (C) is 100 mass %).

[0076] The resin material contained in the substrate layer (C) may be a biodegradable resin. Examples of biodegradable resins include polybutylene adipate-butylene terephthalate copolymer (PBAT), polyhydroxybutyrate, polycaprolactone, polyhydroxyalkanoate, polyglycolic acid, modified polyvinyl alcohol, starch, cellulose, and the like. The material constituting the substrate layer (C) may contain one biodegradable resin or may contain two or more biodegradable resins, and the blending ratio when containing two or more biodegradable resins is not particularly limited.

[0077] <Multilayer structure>

[0078] The thickness of the multilayer structure of the present invention is preferably 30 to 1000 μm. The thickness of the starch layer (A) is preferably 20 to 500 μm, and the thickness of the substrate layer (C) is preferably 10 to 500 μm. If the thickness of the starch layer (A) is within the above range, it tends to have good gas barrier properties. In addition, if the thickness of the substrate layer (C) is within the above range, it is difficult to cause substrate rupture.

[0079] The thickness of the adhesive layer (B) is preferably 5 to 50 μm, more preferably 10 to 30 μm. If it is 5 μm or more, sufficient interlayer bonding strength can be easily obtained, and if it is 50 μm or less, it is difficult to produce a poor appearance called whisker burr during the stamping process of the container after thermoforming, so it is preferred.

[0080] The layer structure of the multilayer structure layer is not particularly limited as long as it is a structure containing starch layer (A), adhesive layer (B) and substrate layer (C) in sequence. When starch layer (A) is denoted as A, adhesive layer (B) is denoted as B, and substrate layer (C) is denoted as C, for example, 3-layer structure of A / B / C, 5-layer structure of A / B / C / B / A, A / B / A / B / C, C / B / A / B / C, etc. can be listed. In addition, the layer (D) other than starch layer (A), adhesive layer (B), and substrate layer (C) can also be contained. When layer (D) is referred to as D, structures such as D / A / B / C, D / B / A / B / C, A / D / B / C, A / B / D / B / C, A / B / D / C, A / B / D / B / C, A / B / C / D, A / B / C / B / D, A / B / C / B / D, D / A / B / C / D, and D / B / A / B / C / B / D can be cited. Among them, structures such as D / A / B / C, A / B / C / D, and D / A / B / C / D, in which A and B are adjacent and B and C are adjacent, are preferred. As layer (D), there is no particular limitation, and for example, paper can be cited. There is no particular limitation on paper, and for example, glassine paper, kraft paper, high-quality paper, medium-quality paper, embossed paper, coated paper, carbonless paper, and paperboard can be cited.

[0081] The peel strength (P1) between the starch layer (A) and the adhesive layer (B) after the multilayer structure of the present invention is placed at a temperature of 23 ° C and a humidity of 50% RH for 1 week is preferably 1.0 kgf / 15 mm or more. In addition, the peel strength (P2) between the starch layer (A) and the adhesive layer (B) after the multilayer structure of the present invention is placed at a temperature of 40 ° C and a humidity of 15% RH for 48 hours is preferably 0.5 kgf / 15 mm or more. In addition, the reduction rate of the peel strength expressed by the following formula is usually less than 60%, preferably less than 50%, and more preferably less than 30%. The above-mentioned peel strength can be measured, for example, by the method described in the embodiments described later.

[0082] Reduction rate of peel strength

[0083] =100×[peel strength (P1)-peel strength (P2)] / peel strength (P1).

[0084] <Method for producing multilayer structure>

[0085] The method for preparing the multilayer structure of the present invention is not particularly limited. For example, a method comprising the following steps can be cited: a step of coextruding the adhesive layer (B) and the substrate layer (C), and then coating the adhesive layer (B) side on the starch layer (A). In addition, for example, a method comprising the following steps can also be cited: a step of extruding the adhesive layer (B), and then coating the adhesive layer (B) between the starch layer (A) and the substrate layer (C).

[0086] In the process of co-extruding the adhesive layer (B) and the substrate layer (C), for example, a two-component two-layer co-extrusion cast film-making device (extruder manufactured by Research Laboratory of Plastics Technology Co., Ltd.) can be used (extruder (1) for substrate layer (C): single shaft, screw diameter 40 mm, L / D=32, extruder (2) for adhesive layer (B): single shaft, screw diameter 32 mm, L / D=26). The temperature conditions of the extruder can be appropriately set according to the thermoplastic resin used. For example, when using extruder (1) to extrude PET (polyethylene terephthalate) for the substrate layer (C), the barrel temperature can be set to 250~270°C, the adapter temperature can be set to 270°C, and the die temperature can be set to 275°C.

[0087] In addition, for example, when the adhesive layer (B) is extruded with a polyolefin using an extruder (2), the barrel temperature can be set to 175 to 270° C., the adapter temperature can be set to 270° C., and the die temperature can be set to 275° C. In addition, the absolute value of the difference between the die temperature of the extruder (1) and the die temperature of the extruder (2) is preferably within 10° C., more preferably 0° C. For example, when the optimum die temperature of the resin used in the extruder (1) and the resin used in the extruder (2) are different, it is preferred to adjust the die temperature using the one with the higher optimum die temperature.

[0088] Then, in the step of coating the adhesive layer (B) side on the starch layer (A), for example, the adhesive layer (B) side of the coextruded laminate can be drawn and coated on the starch layer (A), and then laminated with a nip roll. The drawing speed is preferably 1 to 10 m / min.

[0089] <Packaging Container>

[0090] The packaging container of the present invention contains the multilayer structure of the present invention. The packaging container may consist only of the multilayer structure of the present invention, or may be compounded with other materials. For example, the multilayer structure of the present invention may be thermoformed to form a packaging container. As a thermoforming method, there is no particular limitation, and general vacuum forming and pressure forming can be listed, or as their application, a plunger-assisted method in which a plunger is brought into contact with one side of the multilayer structure to perform molding, or a method called multi-mold molding in which a pair of male and female molds are brought into contact with both sides of the multilayer structure to perform molding, etc. can be listed. In addition, as a method for heating and softening the multilayer structure before molding, non-contact heating or direct heating can be listed, and as non-contact heating, radiation heating using an infrared heater or the like can be listed. In addition, as direct heating, well-known heating methods such as hot plate heating in direct contact with a hot plate can be applied.

[0091] The packaging container composed of the multilayer structure of the present invention can maintain peel strength even when stored under low humidity, so it is excellent as a packaging container. In addition, in a preferred embodiment, it is particularly preferably used as a packaging container for food because of its excellent oxygen barrier properties and biodegradability. Example

[0092] The present invention will be described in more detail below with reference to the following examples etc., but the present invention is not limited to these examples etc. in any way.

[0093] <Tensile elastic modulus of substrate layer (C)>

[0094] The resin material used as the base material layer (C) was extruded using a uniaxial extruder (extruder manufactured by Research Laboratory of Plastics Technology Co., Ltd., diameter 40 mm, L / D=25) under the conditions described in Table 1 below.

[0095] [Table 1]

[0096]

[0097] PHA: 3-Hydroxybutyrate-3-Hydroxyhexanoate Copolymer

[0098] The extruded resin was discharged onto a casting roll to prepare a single-layer film of the substrate layer (C) having a thickness of 30 μm. A commercially available film of Nature Flex NK19 (thickness of 20 μm) was used as the cellophane.

[0099] The obtained film was stored in a conditioning room at 23°C and 50% RH for one week for humidity conditioning, and then cut into 15 mm wide and 150 mm long test pieces. The tensile modulus of the test piece was measured using a tensile testing machine (Instron Corporation, INSTRON 3367) at a speed of 20 mm / min and a distance between chucks of 50 mm. The same test was performed 5 times in total, and the average value was taken as the value of the tensile modulus of elasticity.

[0100] <Peel Strength of Multilayer Structure (Normal Wetness)>

[0101] The multilayer structures produced in Examples and Comparative Examples were stored in a conditioning room at 23° C. and 50% RH for one week for humidity control, and then cut into 15 mm×150 mm pieces to prepare test pieces.

[0102] For the starch layer (A) of multilayer structure and the interlayer of adhesive layer (B), use tensile testing machine (Instron Corporation system, INSTRON 3367), under the condition that speed is 50mm / minute, distance between chucks is 50mm, peeling angle is 180 °, interlayer peeling is carried out, thereby implementing peel strength measurement.Carry out 5 identical tests in total, using average value as the value of peel strength.

[0103] <Peel Strength of Multilayer Structure (Low Humidity)>

[0104] The multilayer structures prepared in Examples and Comparative Examples were stored in a conditioned room at 23° C. and 50% RH for one week for humidity control and further stored in a conditioned room at 40° C. and 15% RH for 48 hours for humidity control, and cut into 15 mm×150 mm pieces to prepare test pieces.

[0105] The peel strength value was determined by the same method as in the above-mentioned <Peel Strength of Multilayer Structure (Normal Wetness)> except that the test piece used was changed.

[0106] It should be noted that the required values ​​of the peel strength of the packaging material under low humidity and normal humidity vary depending on the product shape. For example, in a tray-shaped packaging material obtained by thermoforming the multilayer structure of the present invention, it is preferably 1.5 kgf / 15 mm or more, and in a soft packaging material composed of the multilayer structure of the present invention, 0.5 kgf / 15 mm or more is a preferred target. Although this reference value increases or decreases according to the application, a peel strength of less than 0.4 kgf / 15 mm cannot meet the required performance of most product shapes and applications.

[0107] <Density of Thermoplastic Resin Constituting Adhesive Layer (B)>

[0108] Thermoplastic resin pellets were measured by a dry measurement method using gas (helium) at an apparatus temperature of 25° C. (±1° C.) using AccuPyc II1340 manufactured by Shimadzu Corporation. The same test was performed three times in total, and the average value was taken as the density value.

[0109] <Acid Value of Material Constituting Adhesive Layer (B)>

[0110] 400 mg of the thermoplastic resin constituting the adhesive layer (B) was weighed in a conical flask and added with 80 ml of xylene. The mixture was stirred and heated to 130°C to dissolve the thermoplastic resin. A small amount of phenolphthalein was added to the solution and titrated with a 0.05 mol / L potassium hydroxide-ethanol solution to determine the acid value.

[0111] <UV fading meter test (yellowing) of multilayer structure>

[0112] The multilayer structures produced in Examples and Comparative Examples were stored in a conditioning room at 23° C. and 50% RH for one week to adjust the humidity, and then cut into 50 mm×100 mm pieces to prepare test pieces.

[0113] The UV fading meter (Suga Test Instruments Co., Ltd., U48H) was used to measure the color of the samples at an irradiation intensity of 0.70 W / m 2 The starch layer (A) side of each test piece was irradiated with ultraviolet rays under the conditions of a black panel temperature of 63±3° C. and an irradiation time of 100 hours to carry out measurement, and yellowing was visually evaluated.

[0114] <Preparation of Starch Layer (A)>

[0115] The material of starch layer (A) is modulated by the following method. The modified starch (i) [ECOFILM (registered trademark), Ingredion, corn starch modified with propyl oxide (propylene oxide), straight chain starch content of 70% by mass] in the material constituting the starch layer (A) is 40% by mass to 70% by mass, and the water-soluble resin (ii) [polyvinyl alcohol solution viscosity is 30mPa·s, saponification degree is 99%] is 5% by mass to 35% by mass. Mix in a drum mixer for 2 hours. The powder obtained by mixing is supplied to the feed hopper of the extruder via a weight feeder at a speed of 3.5kg / hour. Water is passed through a liquid delivery pump in a manner such that the amount of water is 25% by mass relative to the total mass of powder and water, sprayed into the barrel of the extruder, and the material of starch layer (A) is modulated in the barrel.

[0116] Extruded from the die head of the extruder, cooled, and set the pulling speed so that the thickness after drying is 150 μm, thereby obtaining a starch layer (A). The barrel temperature during the preparation of the starch layer (A) is set to the temperature distribution as described in Table 2 below. C5~C9 is a cooking treatment area.

[0117] [Table 2]

[0118] Temperature distribution (℃)

[0119]

[0120] <Example 1>

[0121] PET (polyethylene terephthalate) (Traytuf 7300 manufactured by M&G CHEMICALS SA) was used as the material of the base layer (C), and polyolefin (Admer SE800 manufactured by Mitsui Chemicals, Inc.) was used as the material of the adhesive layer (B).

[0122] Co-extrusion is performed by extruding the material of the substrate layer (C) at a barrel temperature of 250°C to 270°C, an adapter temperature of 270°C, and a die temperature of 275°C, and extruding the material of the adhesive layer (B) at a barrel temperature of 175°C to 270°C, an adapter temperature of 270°C, and a die temperature of 275°C, to obtain a laminated film consisting of the adhesive layer (B) and the substrate layer (C) [adhesive layer (B) thickness 20 μm / substrate layer (C) thickness 150 μm].

[0123] The adhesive layer (B) side of the laminated film is coated on the 150 μm starch layer (A) film obtained in the above <Preparation of starch layer (A)>, and they are bonded together using a clamping roller to produce a multilayer structure [starch layer (A) thickness 150 μm / adhesive layer (B) thickness 20 μm / substrate layer (C) thickness 150 μm] at a pulling speed of 3 m / min.

[0124] <Example 2>

[0125] A multilayer structure was prepared in the same manner as in Example 1 except that the material of the adhesive layer (B) was changed to polyolefin (Admer SE810 manufactured by Mitsui Chemicals, Inc.).

[0126] <Example 3>

[0127] A multilayer structure was prepared in the same manner as in Example 1 except that the material of the adhesive layer (B) was changed to polyolefin (Admer SF741 manufactured by Mitsui Chemicals, Inc.).

[0128] <Example 4>

[0129] A multilayer structure was prepared in the same manner as in Example 1 except that the material of the adhesive layer (B) was changed to polyolefin (Admer SF725 manufactured by Mitsui Chemicals, Inc.).

[0130] <Example 5>

[0131] A multilayer structure was prepared in the same manner as in Example 4 except that the material of the substrate layer (C) was changed to PBS (polybutylene succinate) (PBSFZ91 manufactured by Mitsubishi Chemical Corporation) and extrusion was performed at a barrel temperature of 180°C to 200°C, an adapter temperature of 200°C, and a die temperature of 200°C.

[0132] <Example 6>

[0133] The material of the substrate layer (C) was changed to PLA (polylactic acid) (ECOLOJU SA104 manufactured by Mitsubishi Chemical Corporation), and the extrusion conditions were changed (extruder barrel temperature 180°C to 200°C, adapter temperature 200°C, die temperature 200°C).

[0134] In addition, a multilayer structure was prepared in the same manner as in Example 4 except that the extrusion conditions of the polyolefin (Admer SF725 manufactured by Mitsui Chemicals, Inc.) used as the material of the adhesive layer (B) were changed (extruder barrel temperature 175-200°C, adapter temperature 200°C, die temperature 200°C).

[0135] <Example 7>

[0136] As the material of the adhesive layer (B), a polyolefin (Admer SF725 manufactured by Mitsui Chemicals, Inc.) was subjected to single-layer extrusion (extruder barrel temperature of 160°C to 200°C, adapter temperature of 200°C, and die head temperature of 200°C), and the adhesive layer (B) was coated on the starch layer (A). Next, as the substrate layer (C), a cellophane (Nature Flex NK19 manufactured by Futamura Chemical Co., Ltd.) having a thickness of 20 μm was sand-laminated on the adhesive layer (B) surface to produce a multilayer structure.

[0137] <Example 8>

[0138] The material of the substrate layer (C) was changed to PHA (3-hydroxybutyrate-3-hydroxyhexanoate copolymer) (PHBH 151N manufactured by Kaneka Corporation), and the extrusion conditions were changed (the extruder barrel temperature was 130°C to 160°C, the adapter temperature was 160°C, and the die temperature was 160°C). The extrusion conditions of the material of the adhesive layer (B), i.e., polyolefin (Admer SF725 manufactured by Mitsui Chemicals, Inc.), were changed (the extruder barrel temperature was 150 to 160°C, the adapter temperature was 160°C, and the die temperature was 160°C). In addition, a multilayer structure was prepared in the same manner as in Example 4.

[0139] <Example 9>

[0140] The material of the substrate layer (C) was changed to PBAT (polybutylene adipate-terephthalate copolymer) (Ecovio FT2341 manufactured by BASF), and the extrusion conditions were changed (the extruder barrel temperature was 160°C to 200°C, the adapter temperature was 200°C, and the die temperature was 200°C). The extrusion conditions of the material of the adhesive layer (B), i.e., polyolefin (AdmerSF725 manufactured by Mitsui Chemicals) were changed (the extruder barrel temperature was 160°C to 200°C, the adapter temperature was 200°C, and the die temperature was 200°C). In addition, a multilayer structure was prepared in the same manner as in Example 4.

[0141] <Example 10>

[0142] The material of the substrate layer (C) was changed to LDPE (polyolefin) (NOVATEC LD LJ400 manufactured by Japan Polyethylene Corporation), and the extrusion conditions were changed (the extruder barrel temperature was 160°C to 200°C, the adapter temperature was 200°C, and the die temperature was 220°C). The extrusion conditions of the material of the adhesive layer (B), i.e., polyolefin (Admer SF725 manufactured by Mitsui Chemicals, Inc.), were changed (the extruder barrel temperature was 160 to 220°C, the adapter temperature was 220°C, and the die temperature was 220°C). Here, the die temperature was set in accordance with the material with the higher required temperature (here, the adhesive layer (B)). Other than that, a multilayer structure was prepared in the same manner as in Example 4.

[0143] <Example 11>

[0144] A multilayer structure was prepared in the same manner as in Example 4 except that a polyolefin (Admer SF725 manufactured by Mitsui Chemicals, Inc.) and another polyolefin (Admer NF567 manufactured by Mitsui Chemicals, Inc.) were dry-blended at a mass ratio of 75:25 as the material for the adhesive layer (B).

[0145] <Example 12>

[0146] A multilayer structure was produced in the same manner as in Example 4 except that polyolefin (Admer SE800 manufactured by Mitsui Chemicals, Inc.) and LDPE (polyolefin) (NOVATEC LD LC600A manufactured by Japan Polyethylene Corporation) were dry-blended at a mass ratio of 75:25 and used as the material for the adhesive layer (B).

[0147] <Comparative Example 1>

[0148] A multilayer structure was prepared in the same manner as in Example 1 except that the material of the adhesive layer (B) was changed to polyolefin (Lotader 4503 manufactured by Arkema KK).

[0149] <Comparative Example 2>

[0150] A multilayer structure was prepared in the same manner as in Example 1 except that the material of the adhesive layer (B) was changed to polyolefin (Amplify TY4351 manufactured by The Dow Chemical Company).

[0151] <Comparative Example 3>

[0152] A multilayer structure was prepared in the same manner as in Example 1 except that the material of the adhesive layer (B) was changed to polyolefin (Bynel 21E830 manufactured by DuPont de Nemours, Inc.).

[0153] <Comparative Example 4>

[0154] Polyethylene terephthalate (Traytuf 7300 manufactured by M&G CHEMICALS SA) was used as the material of the base material layer (C), and a polyurethane adhesive (MOR Free PU Adhesive manufactured by Rohm and Haas) was used as the material of the adhesive layer (B).

[0155] The material of the substrate layer (C) is extruded at a barrel temperature of 250°C to 270°C, an adapter temperature of 270°C, and a die temperature of 275°C to produce a sheet with a thickness of 150 μm. The material of the adhesive layer (B) is coated on the substrate layer (C) with a thickness of 15 μm by dry lamination. The adhesive layer (B) side of the laminated film composed of the adhesive layer (B) and the substrate layer (C) is laminated to the starch layer (A) film with a thickness of 150 μm obtained in the above <Production of starch layer (A)> using a nip roller to produce a multilayer structure (starch layer (A) thickness 150 μm / adhesive layer (B) thickness 15 μm / substrate layer (C) thickness 150 μm).

[0156] <Comparative Example 5>

[0157] A multilayer structure was produced in the same manner as in Example 4 except that polyolefin (Admer SE800 manufactured by Mitsui Chemicals, Inc.) and LDPE (polyolefin) (NOVATEC LD LC600A manufactured by Japan Polyethylene Corporation) were dry-blended at a mass ratio of 50:50 and used as the material for the adhesive layer (B).

[0158] Various evaluations were performed on the multilayer structures produced in Examples 1 to 12 and Comparative Examples 1 to 5. The results are shown in Table 3. When the adhesive layer (B) contains two types of thermoplastic resins, the density thereof represents a weighted average value in consideration of the composition ratio of the thermoplastic resins.

[0159] [Table 3]

[0160]

[0161] As shown in Table 3, the multilayer structure was left to stand in a thermostatic chamber at 40°C and 15% RH for 48 hours. As a result, it was confirmed that the material constituting the adhesive layer (B) in Examples 1 to 12 contained 0.920 g / cm 3 When the thermoplastic resin is less than 100%, and the acid value of the material is 0.3 mgKOH / g or more, the reduction rate of the peel strength is low, and the peel strength can be maintained even when stored under low humidity. In addition, it does not yellow and has a good appearance.

Claims

1. A multilayer structure comprising, in sequence, a starch layer (A), an adhesive layer (B) and a substrate layer (C), wherein: The material constituting the starch layer (A) contains starch and water. The material constituting the adhesive layer (B) is a material with a density of 0.920 g / cm 3 The following polyolefin polymer, wherein the polyolefin polymer comprises a polyolefin polymer modified with an unsaturated dicarboxylic acid or an anhydride thereof, wherein the acid value of the material constituting the adhesive layer (B) is 0.3 mgKOH / g or more, The substrate layer (C) is a layer having a tensile elastic modulus of 100 MPa or more. The starch layer (A) contains starch in an amount of 20% by mass or more, and contains amylose in an amount of 50% by mass or more.

2. The multilayer structure according to claim 1, wherein The material constituting the starch layer (A) contains at least one water-soluble polymer.

3. The multilayer structure according to claim 1 or 2, wherein The material constituting the starch layer (A) contains at least one kind of clay.

4. The multilayer structure according to claim 1 or 2, wherein The material constituting the substrate layer (C) includes at least one selected from the group consisting of polyethylene terephthalate, polylactic acid, polyethylene, polypropylene, cellophane, aromatic polyester, and polybutylene succinate.

5. A method for preparing a multilayer structure, which is a method for preparing a multilayer structure according to any one of claims 1 to 4, the method comprising: a step of co-extruding the adhesive layer (B) and the substrate layer (C), and Next, the adhesive layer (B) is coated on the starch layer (A).

6. A method for preparing a multilayer structure, which is a method for preparing a multilayer structure according to any one of claims 1 to 4, the method comprising: The step of extruding the adhesive layer (B), and Next, a step is performed to apply an adhesive layer (B) between the starch layer (A) and the base material layer (C).

7. A packaging container comprising the multilayer structure according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Multilayer film

    JP2015508341A

  • Food packaging

    JP2015533733A

  • Multilayer Films

    US20140349047A1

  • Methods for producing paper containers for liquid, and paper containers for liquid

    US20190176455A1